2017
DOI: 10.9775/kvfd.2017.17752
|View full text |Cite
|
Sign up to set email alerts
|

Ratlarda Metoraksat Kaynaklı Testiküler Toksisite Üzerine Hesperidinin Etkisi

Abstract: Citation of This ArticleBelhan S, Özkaraca M, Kandemir FM, Gülyüz F, Yıldırım S, Ömür AD, Yener Z: Effectiveness of hesperidin on methotrexate-induced testicular toxicity in rats. Kafkas Univ Vet Fak Derg, 23 (5): 789-796, 2017789-796, . DOI: 10.9775/kvfd.2017 AbstractThe aim of this study was to investigate the effect of hesperidin on male reproductive system in rats to which methotrexate (MTX) was administered. In the study, 28 male Wistar albino rats at the age of 8 weeks and had 250-300 g of live weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…8-OHdG expressions in the Cd group were severely observed. The expression of 8-OHdG in this toxicity is consistent with the literature (Belhan et al, 2017;Belhan et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…8-OHdG expressions in the Cd group were severely observed. The expression of 8-OHdG in this toxicity is consistent with the literature (Belhan et al, 2017;Belhan et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…8-OHdG concentrations of a cell reveal a significant measure of oxidative stress. The 8-OHdG expressions have been reported to be severe in testis tissue in oxidative damage (Belhan et al, 2017;Saripinar et al, 2017). In this study, 8-OHdG expressions were immunohistochemically observed to determine the oxidative damage in testes.…”
Section: Discussionmentioning
confidence: 99%
“…NFκB is thus considered an impor tant regulator of inflammation. 13 MTX was reported to induce a marked rise in the inflammatory mediators like IL6 and IL1β in testicular tissues 10,13,15,39 along with upregulation of the NFκB mRNA and protein testicular expressions. 13,15 In our study, MTX induced a marked testicular inflammation response which was confirmed by the marked elevation in the inflammatory markers of IL6 and IL1β testicular levels as well as the marked upregulation of the testicular NFκB expression, which was in harmony with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the release of pro-inflammatory cytokines like interleukin-6 (IL-6) and IL-1β along with cell death through apoptotic cascades was also documented in the pathophysiology of MTX-induced testicular injury. 10,13,15 Apoptosis is known as a process of programmed cell death and regulated by the family members of bcl-2 which has been documented to be involved in the testicular apoptosis. 16 -18 Bcl-2 has been reported to inhibit apoptosis and prolong cell survival while bcl-2 associated x protein (Bax) could block the capability of bcl-2 in inhibiting apoptosis and could be considered as an apoptosis regulator.…”
Section: Introductionmentioning
confidence: 99%
“…Adding an antioxidant medication to MTX treatment regimen may be the solution to reduce or prevent the side effects of MTX. Many researchers have studied effect of different substances such as against oxidative damage of MTX in testes [10,11,18,31,34,[37][38][39][40][41][42][43][44]. MTX + caffeic acid phenethyl ester (CAPE) treatment caused the oxidative stress to increase in the testicles despite the antioxidant, antiinflammatory properties of CAPE [31].…”
Section: Discussionmentioning
confidence: 99%